DEVELOPMENT OF POWTOON AUDIO-VISUAL LEARNING MEDIA ON THE THEME OF MY HERO IN CLASS IV OF SD NEGERI SERANG 14 - Yayah Sunaiyah; Ujang Jamaludin; Reksa Adya Pribadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to develop PowToon audio-visual media on the theme of my hero and determine the teacher's involvement in the media, the response of students in using PowToon audio-visual media in learning, and determine the feasibility of the media developed. In this study using the development method or in English Research & Development, the research and development method is a research method used to produce certain products and test the effectiveness of these media (Sugiyono, 2016, p. 297). Based on the feasibility results that have been carried out by a team of media experts, material experts, and linguists. The results of research conducted by media experts obtained an average score of 89%, validation by material experts received an average score of 81%, and the results of linguist validation received an average score of 88%. The results of the student response questionnaire in the limited trial received a score of 93% and in the operational field trial received a score of 96%. This research shows that this research produces media products in the form of audio-visual PowToon on the theme of my hero. The percentage of feasibility results of media expert validation includes the "Very Feasible" category; material experts include the "Very Feasible" category; linguists include the "Very Feasible" category. The percentage of student’s responses is included in the “Very Good” category. Therefore, the media is declared suitable as media in the learning process in elementary schools.